Influence of Board of Management Governance Practices on Students' Performance in Kenya Certificate of Secondary Education in Athi River Sub-County, Kenya - Mutindi, Mutuku T.; Kanori, Mr. Edward; Kalai, Dr. Jeremiah M. (African Journal of Education and Practice, 2016)
Purpose: The purpose of this study was to investigate the influence of Board of management governance practices on students' performance in Kenya Certificate of Secondary Education in Athi River Sub-county, Kenya. Methodology: The research used descriptive survey design. The study targeted 13 public secondary schools in Athi-River Sub-county. The target population was 208 Board of Management members, 13 Board of management chairpersons, 13 principals and 260 teachers in Athi-River Sub-county secondary schools. Stratified random sampling technique was used to select 13 schools to ensure that all the schools were well represented according to the various regions. Census technique was used to select all the 13 principals and 13 Board of management chairpersons. Simple random sampling was used to select 97 other Board of management members and 132 teachers. The sample size of this study was therefore 255 respondents. The Statistical Package for Social Sciences (SPSS) software version 20.0 was used to carry data analysis. Results: The findings revealed that provision of incentives to teachers, provision of rewards to students, involving teachers in target setting and provision of learning resources were found to be satisfactory variables in explaining students performance. This was supported by coefficient of determination also known as the R square of 48%. Regression of coefficients results showed that provision of enough learning resources and students' performance was highly correlated, positively and significantly related. Provision of incentives, rewards, target setting and students' performance were also positively and significantly. Unique contribution to theory, practice and policy: The study recommended that the training institutes like KEMI should organize tailor made courses for BOM members to equip them with the right knowledge on best governance practices in schools.